Deconstructing sportswashing: Analytical concept or ideological prejudice? - Moriconi, M. (The Palgrave handbook on the economics of manipulation in sport, 2024)
Sportswashing has become a fashionable concept when discussing the use of sport for political purposes, especially in the anglophone media. Its fame led to the Norwegian Language Board choosing sportswashing as word of the year in 2021. In 2022, the term increased in popularity as did its presence in public discourse, especially with the holding of the FIFA World Cup in Qatar. It even reached the social sciences where an incipient production of articles on the subject has emerged. Despite the prevalence of the term, there is almost no debate around the nature of the concept. Its definition is somewhat limited and contradictory, and its utility generates more doubts than certainties. Given this framework, this chapter presents a critical deconstruction of the concept by denoting the semantic contradictions, analysing the practices and the actors described by journalists and activists, and promoting a non-ideological and critical way of analysing how governments use sport.